A fenomenologia da sociedade da informação e a responsabilidade civil à luz da Lei n.12.965/14 – Marco Civil da Internet - Rotundo, Rafael Pinheiro (2018)
The technological advancement provided by the global computer network has revolutionized human activities, communications have become easier, territorial boundaries between countries do not exist in the virtual world, and trade has been driven on a global scale. In this revolutionary network context, problems of high complexity arise that threaten the safety of users and the system itself. The lack of control and anonymity created a false impression that the internet would be an environment without rules, in which the wrong would not be grieved. In this context, civil liability for damages on the Internet is a subject that the law can’t refrain from dealing with, since its dynamism must be careful to protect and protect any offense that causes imbalance. At a first moment the work will address the characteristics of the information society, how the interpersonal relationships were affected by the digital age, and then to address the technical issues of the Internet, its operation, what services are available, its operators and other agencies. In a second moment, it will be approached to the civil responsibility of its evolution in counterpart to the society of the information, developing its study, as well as the elements that integrate it, with the action or omission, damage and causal link. Therefore its repercussions before entering the legal world of the Internet Civil Law, Law 12.965/2014, its interpretation by the STJ and the treatment of the subject in other countries